2018
DOI: 10.3389/fmicb.2018.01210
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Markers in Obese Adolescent and Adult Patients: Age-Dependent Differential Patterns

Abstract: Obesity levels, especially in children, have dramatically increased over the last few decades. Recently, several studies highlighted the involvement of gut microbiota in the pathophysiology of obesity. We investigated the composition of gut microbiota in obese adolescents and adults compared to age-matched normal weight (NW) volunteers in order to assemble age- and obesity-related microbiota profiles. The composition of gut microbiota was analyzed by 16S rRNA-based metagenomics. Ecological representations of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
119
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(144 citation statements)
references
References 64 publications
20
119
2
3
Order By: Relevance
“…The observation of lower relative abundances of Anaerofilum , Gemellaceae , Streptococcaceae , and Rikenellaceae in the obese group is consistent with the report by Del Chierico et al , which demonstrated higher levels of Rikenellaceae in individuals of average weight compared to overweight subjects . However, contrary to a previous report, the relative abundance of Streptococcaceae was higher in mice with NASH on a high‐fat diet.…”
Section: Discussionsupporting
confidence: 90%
“…The observation of lower relative abundances of Anaerofilum , Gemellaceae , Streptococcaceae , and Rikenellaceae in the obese group is consistent with the report by Del Chierico et al , which demonstrated higher levels of Rikenellaceae in individuals of average weight compared to overweight subjects . However, contrary to a previous report, the relative abundance of Streptococcaceae was higher in mice with NASH on a high‐fat diet.…”
Section: Discussionsupporting
confidence: 90%
“…increases in the overweight phenotype [49]. Moreover, high abundance of Blautia is associated with glucose intolerance and the presence of Blautia is positively correlated with Type 2 diabetes [50,51]. Our data were consistent with this result and indicated that CO/TC might suppress Mucispirillum and Blautia colonization in the intestine which may have a beneficial effect.…”
Section: Discussionsupporting
confidence: 87%
“…Undigested food is fermented by the gut microbiota producing various microbial metabolites such as short-chain fatty acids such as acetate, propionate, azelate, while others may be co-produced by bacteria and by the host such as butyrate and hippurate [52][53][54][55]. In particular, intestinal micro-organisms produce benzoate [56,57], that the host conjugates with glycine through glycine N-acyltransferase [58], whose gene is less expressed in women than in men [59].…”
Section: Discussionmentioning
confidence: 99%